Discourse Analysis Of Nahdlatul Ulama Identity Construction On Instagram In 2024 East Java Gubernatorial Election - Sutrisno; Agus Mahfud Fauzi (Journal of Public Power, 2026)
East Java is a highly significant political arena for Nahdlatul Ulama due to its pesantren ecology, networks of kiai, and affiliate organizations which possess strong social proximity and influence. As a base for nahdliyin citizens, East Java becomes a contested arena for gubernatorial candidate pairs to gain public sympathy. In fact, during the process, all candidate pairs claim to represent the nahdliyin community in East Java. Meanwhile, Instagram as a social media platform has become an intensive visual political campaign medium to win over the wider public. This research aims to explain how Nahdlatul Ulama identity is constructed, contested, and disseminated through Instagram during the 2024 East Java Gubernatorial Election. Therefore, this study examines the phenomenon of NU identity being contested by East Java gubernatorial and vice-gubernatorial candidates using a qualitative approach with critical discourse analysis. The theoretical framework combines Stuart Hall's representation theory and Michel Foucault's reading of power relations to analyze meaning production, symbolic legitimation, and truth regimes in digital space. The findings show three main patterns in the construction of NU identity on Instagram: an authoritative-institutional pattern, a hybrid nationalist-santri pattern, and a nahdliyin-populist authenticity pattern. Across these patterns, all three utilize symbolic meanings such as pesantren, kiai, songkok, the color green, sowan, and santri symbols as capital to gain legitimacy from the nahdliyin community. However, these symbols render the contestation of ideas, substantive policies, and concepts superficial. Thus, Instagram not only functions as a campaign medium but also as an arena for simplifying NU identity into electoral symbols